Qualitative and Quantitative Assessment of Common Weed Species in West Gondar Sesame Growing Area, Ethiopia - Ambaw, Asfaw; Ebabuye, Yohannes; Abeje, Yimer (ABC Journal of Advanced Research, 2020)
Weeds compete with crops grown for resource limits such as water, nutrients, and light. Weed infestation is one of the major factors limiting sesame production, as its seedlings grow slowly during the first few weeks making it a weak competitor at earlier crop growth stages. Weed induced sesame yield reductions of up to 65 percent, and a need for a crucial weed-free duration of up to 50 days following planting. Weed surveys are useful for determining the occurrence and relative importance of weed species in crop production systems. Weed survey on a farm basis is needed to establish efficient weed management and decision making mechanisms and to evaluate weed control measures. Therefore this survey was conducted to assess qualitative and quantitative weed species in sesame growing areas of west Gondar, Ethiopia. Weed survey was conducted in 2012 at Metema and 2013 main cropping season at Metema, Tach Armachiho, and Mirab Armachiho district. data on weed species type and count were taken along the diagonal with 50cm x 50cm quadrate at a 15-meter interval at three points. Visual identification, manuals, photographs, leaflets, and books were used for identifying weed species. They conducted interviews with farmers, development agents, and district experts working in the region. Weed species compositions were analyzed by frequency, abundance, dominance, and similarity index. In the districts, 31common weed species or groups of species from 17 families were recorded. Ipomea cordofana Br., Grass spp’, Commelina benghalensis L. Andropogon abyssinicus (Fresen) R.Br., Boerhaavia erecta L., Corchorus olitorius L.kudra, Corchorus trilocularis L., Leucas martinicensis (Jacq) ait.f. and Ipomea triloba are the most prevalent, abundant, and important weeds in sesame fields in north Gondar. As to this on-farm and practical training on identification and demonstration management options should be given on the low land of north Gondar farmers.